International Law Analysis of India’s Challenge to the Infrastructure Development Provisions of the National Land Boundary Law - Pu Peng (Studies in Law and Justice, 2023)
Infrastructure development is a necessary path for development in every region, and the disputed sensitive areas between China and India also cannot avoid the topic of infrastructure development. China adheres to the path of peaceful development and thoroughly studies the international law and jurisprudence that promote peaceful conflict resolution, so as to provide international law basis for resolving the dispute between the two sides as soon as possible and for the smooth progress of infrastructure development. Both sides should steadily promote the settlement of the issue in accordance with international law, legally carry out infrastructure construction, and safeguard the livelihood and security of the disputed areas. Clarifying the relevant legal issues is also an important prerequisite for eliminating international biased opinion and better cooperation and negotiation.